Combination Effect of Phenylalanine‐Arginine‐Beta‐Naphthylamide and Curcumin on the Expression of the mexY Gene in Aminoglycoside‐Resistant Clinical Isolates of Pseudomonas aeruginosa - Parisa Charkhi; Mohammad Reza Haghshenas; Bahman Mirzaei; Younes Khalili; Hamid Reza Goli (Health Science Reports)
ABSTRACT Background and Aims Overexpression of MexXY‐OprM efflux pump causes resistance to aminoglycosides in Pseudomonas aeruginosa. We aimed to investigate the relationship between resistance to aminoglycosides and the MexXY‐OprM expression level in P. aeruginosa clinical isolates without and after treatment with curcumin and/or phenylalanine‐arginine‐beta‐naphthylamide (PAβN) as the efflux pump inhibitors. Methods We collected 100 clinical isolates from hospitalized patients. The minimum inhibitory concentrations of aminoglycosides were determined by the micro‐broth dilution method in the presence and absence of PAβN and/or curcumin. Then, real‐time PCR was used to determine the expression level of the MexXY‐OprM efflux pump. Results In this study, 34%, 35%, 10%, 38%, 43%, 42%, and 39% of the clinical isolates were resistant to gentamicin, tobramycin, amikacin, netilmicin, spectinomycin, kanamycin, and streptomycin, respectively. Also, 45% of the isolates showed an overexpression of the mexY gene, while 31 (68.88%) isolates exhibited a 2–3‐fold overexpression, and 14 (31.11%) isolates had a more than threefold overexpression of the mexY gene. However, 4 (8.88%) isolates showed a ≥ 10‐fold overexpression of this gene. The combination of PAβN with spectinomycin, netilmicin, streptomycin, and kanamycin exhibited a reduced MIC range of these aminoglycosides in 93.02%, 86.8%, 76.9%, and 71.4% of resistant isolates, respectively. Additionally, all gentamicin‐, tobramycin‐, kanamycin‐, streptomycin‐, and netilmicin‐resistant isolates showed a decreased MIC range in combination with curcumin. The most synergistic effect of curcumin and PAβN was observed in combination with spectinomycin, while the least synergistic effect was detected with kanamycin. Conclusion Curcumin can be a significant efflux inhibitor as an adjuvant in combination with aminoglycosides for successful treatment of patients infected by P. aeruginosa overexpressing the MexXY‐OprM efflux pump.